Mesospheric dust and its secondary effects as observed by the ESPRIT payload - O. Havnes; L. H. Surdal; C. R. Philbrick; C. R. Philbrick (Annales Geophysicae, 2009)
The dust detector on the ESPRIT rocket detected two extended dust/aerosol layers during the launch on 1 July 2006. The lower layer at height ~81.5–83 km coincided with a strong NLC and PMSE layer. The maximum dust charge density was ~−3.5×109 e m−3 and the dust layer was characterized by a few strong dust layers where the dust charge density at the upper edges changed by factors 2–3 over a distance of ≲10 m, while the same change at their lower edges were much more gradual. The upper edge of this layer is also sharp, with a change in the probe current from zero to IDC=−10−11 A over ~10 m, while the same change at the low edge occurs over ~500 m. The second dust layer at ~85–92 km was in the height range of a comparatively weak PMSE layer and the maximum dust charge density was ~−108 e m−3. This demonstrates that PMSE can be formed even if the ratio of the dust charge density to the electron density P=NdZd /n_e≲0.01.